Striving For an Equal Church: Affective Utopias of Christian Queer Activists in Finland, 1960s–2000s - Alasuutari, Varpu (Foreningen Lambda Nordica, 2026)
In this article, I explore the hopes and aims of Christian queer activists in Finland from the late 1960s to the early 2000s by conceptualising them with the notion of utopia. I approach utopia from the perspective of not-yet-existing and hopeful queer futurity (Muñoz 2009; Jones 2013), tying it together with affect theoretical notions of activism as an affectively motivated aspiration for a better world (Gould 2009). The study makes an empirical contribution to the study of queer activism and the interdisciplinary fields of queer history and queer religious studies, as well as a theoretical contribution to queer theoretical accounts of utopia. As my data, I use oral history interviews, autobiographical writings, and archival materials collected by the activists. As a method of analysis, I utilise close reading informed by affect theory (Berg et al. 2019). I ask: how did utopian thinking appear in the stories of Christian queer activists, who aimed for inclusion and equality in the Evangelical Lutheran Church of Finland? I argue that activism always needs utopias to exist, and that utopian thinking was a central force within the early decades of Christian queer activism in Finland. I show that utopian thinking had both private and public relevance for the Christian queer activists and that by striving for inclusion and equality, the activists represented utopian voices within the Church and the local Christian queer community of the time.